1999
DOI: 10.1007/s003359901028
|View full text |Cite
|
Sign up to set email alerts
|

New insights into porcine-human synteny conservation

Abstract: Eleven genes were mapped to the porcine genome with the aim of improving the human-porcine comparative gene map. Five of these genes were from regions of the human genome painted by porcine chromosomal probes; of these, two mapped to chromosomes not expected from the painting results. Among the six genes from human regions not painted by porcine chromosomal probes, three genes did not map where expected by the principle of parsimony. Several of the gene assignments indicate the existence of small regions of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Thus, we propose that HSA4q is likely to still exhibit the common ancestral gene order for this region of the genome. With the recent mapping of GRIA2, UCP1, PEPS3, GNRHR, and FGF2 on SSC8 (Larsen et al 1999;Rohrer 1999), our proposed scenario receives further support. However, more detailed gene ordering will be required for a definitive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that HSA4q is likely to still exhibit the common ancestral gene order for this region of the genome. With the recent mapping of GRIA2, UCP1, PEPS3, GNRHR, and FGF2 on SSC8 (Larsen et al 1999;Rohrer 1999), our proposed scenario receives further support. However, more detailed gene ordering will be required for a definitive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that SSC1 might have additional regions of conserved synteny that were not detected by the painting between HSA18 and SSC1. In addition, the gene order of the physical and multipoint linkage analyses showed that several markers assigned from HSA15 to SSC1, including FGF7 (SSC1q11-q17) and MEF2A (SSC1q11-q17) (Larsen et al, 1999), are centromeric to MC4R. These results suggest that the location of the MC4R gene might define a boundary between regions on SSC1 corresponding to HSA18 and HSA15.…”
mentioning
confidence: 85%
“…CRSP9 and ETF1 are very close together in both human and mouse, however, they have been mapped to different porcine chromosomes (SSC16 and SSC2) in this experiment. Another gene GRIA1 (glutamate receptor, ionotropic, AMPA 1) which is located in the 5q33 region in human has been assigned to SSC16 (q14 or q22 ] q23) in pig and suggests that this homologous region was in a rather small gap so the signal could not be detected by painting (Larsen et al, 1999). The assignment of porcine CRSP9 may also prove this.…”
Section: Resultsmentioning
confidence: 90%